2023
DOI: 10.1038/s41467-023-38508-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic characteristics of graphene composites—evolution from thermal conductors to thermal insulators

Abstract: The development of cryogenic semiconductor electronics and superconducting quantum computing requires composite materials that can provide both thermal conduction and thermal insulation. We demonstrated that at cryogenic temperatures, the thermal conductivity of graphene composites can be both higher and lower than that of the reference pristine epoxy, depending on the graphene filler loading and temperature. There exists a well-defined cross-over temperature—above it, the thermal conductivity of composites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…For carbon‐based nanofiber films, phonons are dominant in the heat transfer process. [ 47,48 ] However, the nanostructure amplifies the scattering effect on phonons, thereby impeding the ordered transfer of heat between fibers, [ 49 ] as shown in Figure 4a. Consequently, this temperature difference extended to the TE layer as well.…”
Section: Resultsmentioning
confidence: 99%
“…For carbon‐based nanofiber films, phonons are dominant in the heat transfer process. [ 47,48 ] However, the nanostructure amplifies the scattering effect on phonons, thereby impeding the ordered transfer of heat between fibers, [ 49 ] as shown in Figure 4a. Consequently, this temperature difference extended to the TE layer as well.…”
Section: Resultsmentioning
confidence: 99%
“…Percolation at high concentrations was also explored in recent work by Nataj et al , 121 who measured the thermal conductivities of graphene/epoxy composites over a wide range of temperatures, from 2 K to room temperature, and for a range of graphene volume fractions. They showed that at low graphene concentrations, a cross-over temperature existed, below which, the thermal conductivity of the composite decreased with an increase in graphene concentration, and above the cross-over temperature, the thermal conductivity increased with increasing filler loading.…”
Section: Synergistic/percolation Network With Multiple Fillers and Hi...mentioning
confidence: 99%
“…6,7 Owing to these outstanding characteristics, epoxy resins have been applied in a diverse range of fields including transportation, construction, electronics and renewable energy. 8,9 The flammability of epoxy resins, however, limits their application range so as to comply with fire-safety regulations and prevent the release of toxic combustion products. 10,11 Generally, flame-retardant additives have been developed to improve the flame retardancy of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%